1998
DOI: 10.1007/s002619900360
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel varices: report of two cases

Abstract: Two cases of small bowel (S-B) varices associated with portal hypertension, one with liver cirrhosis and one with portal thrombus, are reported. Detection of S-B varices has been a challenging task and several invasive diagnostic techniques have been used for this purpose. However, in our cases, color Doppler sonography revealed the S-B varices supplied by the superior mesenteric vein and draining to the iliac (one case) or ovarian vein (other case), which helped to establish an early appropriate diagnostic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Various treatments have been carried out through the years: portal vein dilatation, portal stenting, bilioenteric reanastomosis, embolization, splenectomy, shunt operation, and endoscopic procedures. [11][12][13][14][17][18][19][20][21][22][23][24][25][26] Neumann et al 13 first reported the treatment using endoscopy. Their case was also a patient with pancreatic cancer whose portal vein was obstructed 1 year after operation.…”
Section: Discussionmentioning
confidence: 99%
“…Various treatments have been carried out through the years: portal vein dilatation, portal stenting, bilioenteric reanastomosis, embolization, splenectomy, shunt operation, and endoscopic procedures. [11][12][13][14][17][18][19][20][21][22][23][24][25][26] Neumann et al 13 first reported the treatment using endoscopy. Their case was also a patient with pancreatic cancer whose portal vein was obstructed 1 year after operation.…”
Section: Discussionmentioning
confidence: 99%